JUDICIAL REVIEW OF CRIMINAL DEFAMATION ACCORDING TO THE LAW OF ELECTRONIC INFORMATION AND TRANSACTION: A CASE STUDY OF FLOURENCE SAULINA SIHOMBING - Puspitasari, Rosiana (Faculty of Law, Universitas Sebelas Maret, 2017)
This study analyses defamation via social media towards Flaurence Saulina Sihombing case. The study raises the elements of contempt in Law Number 11 of 2008 which was converted into Law Number 19 of 2016 con Electronic Information and Transactions (EIT) and compare it with the humiliation under the Criminal Code. The purpose of this study was to determine whether the prosecution on Florence Saulina Sihombing meet the elements of contempt in accordance with the prohibited stipulation under Article 27 paragraph (3) Electronic Information and Transactions Law. This research using normative juridical approach. The source of the data is secondary data source that the data obtained from the literature by studying three legal materials, namely: primary legal materials, secondary legal materials, tertiary legal materials that will be classified and systematized. The conclusion shows that the case Flaurence Saulina Sihombing meet a subjective element in the form of intentionally actions. This actions undertaken by Florence met the element strike action. The object in the form of honour based on Article 27 Law Number 11 of 2008 which was converted into Law Number 19 of 2016 on Electronic Information and Transactions (EIT). The writer tends to confirmly agree with the Yogyakarta District Court via Decision Number 382/Pid.B/2014/PN Yyk of 2015.